Opsonic antibody activity against Actinobacillus actinomycetemcomitans in patients with rapidly progressive periodontitis. - Sjöström, K (1992)
Actinobacillus actinomycetemcomitans has been closely associated with early-onset, severe periodontitis, and such patients often have serum immunoglobulin G (IgG) antibodies reactive with antigens of this gram-negative pathogen. We examined the functionality and potential importance of these antibodies. The opsonic activity against A. actinomycetemcomitans of sera from 30 patients with rapidly progressive periodontitis (RPP) and from 28 periodontally normal subjects was tested by using polymorphonuclear leukocyte (PMN) chemiluminescence and bactericidal assays. Peak chemiluminescence values correlated strongly with killing observed in the PMN-dependent bactericidal assay (r = 0.88; P < 0.001). Neither the mean IgG titer nor the mean peak chemiluminescence differed significantly between the two groups. However, when the relationship between chemiluminescence and titer was examined, regression analysis showed that antibodies present in low-titer normal sera were significantly more effective at opsonizing A. actinomycetemcomitans than antibodies present in low-titer RPP patient sera (P = 0.04). Thus, periodontally normal individuals may be better able than RPP patients to clear A. actinomycetemcomitans in early stages of colonization, and anti-A. actinomycetemcomitans antibodies in RPP patients may be relatively ineffective in preventing infection by this organism.